2019
DOI: 10.1002/nbm.4200
|View full text |Cite
|
Sign up to set email alerts
|

Structure or Exchange? On the Feasibility of Chemical Exchange Detection with Balanced Steady‐State Free Precession in Tissue – An In Vitro Study

Abstract: Balanced steady-state free precession imaging has recently been suggested for chemical exchange detection (bSSFPX). The objective of this work is to investigate the contributions of microstructural, chemical shift and chemical exchange effects to the asymmetry of the bSSFP profile at field strengths of 3 T and 9.4 T. To this end, in vitro bSSFPX experiments are performed for a range of repetition times and flip angles in glucose water solutions with different MnCl 2 concentrations and tissue homogenates obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…This may include simulations and experiments to gain more insights into the possible mechanisms driving the bSSFP profile asymmetry observed in oxygenated blood samples (Figure 4), such as diffusion 14 or chemical exchange effects. 53,54…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may include simulations and experiments to gain more insights into the possible mechanisms driving the bSSFP profile asymmetry observed in oxygenated blood samples (Figure 4), such as diffusion 14 or chemical exchange effects. 53,54…”
Section: Discussionmentioning
confidence: 99%
“…Future studies may focus on analyzing the dependence of MIRACLE‐R 2 on TR and flip angle in more detail, to ultimately establish a quantitative model for given blood oxygenation levels and field strengths. This may include simulations and experiments to gain more insights into the possible mechanisms driving the bSSFP profile asymmetry observed in oxygenated blood samples (Figure 4), such as diffusion 14 or chemical exchange effects 53,54 …”
Section: Discussionmentioning
confidence: 99%
“…33 The results of a recent study investigating the contribution of chemical exchange effects to asymmetric intravoxel frequency distributions in WM corroborate that the main factor driving bSSFP profile asymmetries in WM is structure-and not exchange-related. 35 This inherent sensitivity to tissue microstructure, combined with a mixed dependence on both T 1 and T 2 , as well as the ability to enable distortion-free motion-robust volumetric imaging with high signal-to-noise ratio efficiency in short scan times, 36,37 makes phase-cycled bSSFP an interesting tool for multiparametric mapping of various MR quantities. [38][39][40] Because off-resonance effects in the bSSFP signal arising from B 0 inhomogeneities are used as an additional encoding dimension for multiparametric mapping, phase-cycled bSSFP is well suited for high-resolution imaging at ultrahigh field strength.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that an asymmetric frequency distribution causes asymmetries in the bSSFP frequency profile. [17][18][19] MIRACLE and PLANET fail to account for these anisotropies in the tissue microenvironment, but assume an idealized model for the bSSFP profile, ie, a symmetric frequency response. 15,20 To eliminate this bias, a feedforward artificial neural network (ANN) is trained in this work with phase-cycled bSSFP data acquired at 3T in healthy volunteers as input and a multi-parametric output, ie, T 1 , T 2 , transmit field B + 1 , and off-resonance ∆B 0 , using dedicated reference relaxation time measurements and field maps as targets.…”
Section: Introductionmentioning
confidence: 99%
“…This bias is especially prominent in white matter (WM) and expected to be caused by an asymmetric intra‐voxel frequency content due to fiber tract geometry, in combination with multi‐component relaxation, eg, due to the presence of myelin. It has been reported that an asymmetric frequency distribution causes asymmetries in the bSSFP frequency profile 17‐19 . MIRACLE and PLANET fail to account for these anisotropies in the tissue microenvironment, but assume an idealized model for the bSSFP profile, ie, a symmetric frequency response 15,20 …”
Section: Introductionmentioning
confidence: 99%